Strategic relationships at work : creating your circle of mentors, sponsors, and peers for success in business and life - Kram, Kathy; Murphy, Wendy (McGraw-Hill, 2014)
THE MUST-HAVE GUIDE TO MENTORING For managers. For entry level. For executives. For entrepreneurs. For everyone. With job mobility increasing, globalization expanding, and technology advancing, you need more than a steady job and a solid network to keep your career on track. You need mentors--to learn and to grow--whether you're just starting out, are firmly established, or at the top of your profession. Everyone has something to learn, and everyone has something to teach. Introducing Strategic Relationships at Work: The first comprehensive mentoring guide written specifically for 21st-century career building, this entrepreneurial approach to work relationships addresses the key issues of our time: Job Mobility: How to make personal connections you can transfer from job to job Globalization: What you can learn from new mentors in a larger global context Technology: How to engage with the latest advances in social media and technology Pace of Change: What you can do to keep up--with a little help from your friends Using simple tools and proven strategies, this essential guide shows you how to leverage the relationships you already have to map out a new developmental network that grows with your career. You'll learn the secrets of companies with excellent developmental cultures, including IBM, Procter & Gamble, Sodexo, and KPMG. You'll discover the most effective ways to develop new talent in your workplace through formal programs that leverage mentors, sponsors, coaches, reverse mentors, and mentoring circles. You'll learn how leaders create work cultures where both formal and informal mentoring thrive. And you'll find handy charts and checklists to assess your work, your relationships, and your career path. MENTORING FOR THE NEW MILLENNIUM Whether you plan to move in and out of the workforce, make lateral or nontraditional career moves, or simply want to learn or teach new skills, Strategic Relationships at Work will help you take control of your destiny--and build the career or company that you envision. This powerful guide helps you leverage your interpersonal skills using the most effective tools available. You'll find ready-to-use checklists and worksheets, self-assessments, refl ective exercises, graphs, charts, and other visual tools to map out your own personal network of developers inside and outside of work. This is how you build a career that grows along with you. This is Strategic Relationships at Work. "Receiving and providing m ...